ANALISIS STRATEGI PENGRAJIN KULIT DALAM MENGEMBANGKAN USAHA (Studi Kasus di Sentra Industri Kerajinan Kulit Kelurahan Selosari Magetan) - Rudini Hadinata (Jurnal Ekonomi dan Studi Pembangunan, 2014)
The research was conducted in the leather industry center, at Selosari Village Magetan. The research approach is qualitative research by using a case study approach and Phenomenology. The data used are primary data and secondary data. The primary data obtained from interviews conducted for businesses leather industry, leather industry center chairman, and chairman of the industrial sector Disperindag Magetan. While secondary data obtained from the data archive and Disperindag at Selosari Village Magetan. Keywords: businesses, leather industry